2015
DOI: 10.1016/j.mambio.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Systematic variation in the stable hydrogen isotope (δ2H) composition of fur from summer populations of two species of temperate insectivorous bats

Abstract: extubation. We have observed only a moderate incidence of POUR and a low incidence of urinary infections. In addition, no correlation between POUR and worse outcome has been shown. Our data suggests that thoracic epidural analgesia is not an absolute indication of urinary drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In contrast, fur keratin of juvenile bats was enriched by 1.6‰ in 15 N in relation to 14 N compared to fur keratin of adult females. Finally, fur keratin of juvenile bats was depleted by 13.4‰ in 2 H in relation to 1 H compared to fur keratin of adult females, which is larger than the isotopic differences observed before …”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In contrast, fur keratin of juvenile bats was enriched by 1.6‰ in 15 N in relation to 14 N compared to fur keratin of adult females. Finally, fur keratin of juvenile bats was depleted by 13.4‰ in 2 H in relation to 1 H compared to fur keratin of adult females, which is larger than the isotopic differences observed before …”
Section: Discussionmentioning
confidence: 54%
“…Previous stable isotope studies based on mammalian fur showed an age effect of isotopic composition between juveniles and adults for hydrogen, yet no previous studies in bats included stable nitrogen and carbon isotopes. In agreement with our prediction, stable isotope ratios in fur keratin differed for the three elements between mothers and juveniles of common noctule bats captured at the same maternity roost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of species-specific transfer functions is ideal, as interspecific variation in these functions may impact origin assignment [ 67 ]. While there are strong transfer functions for many species, there is still substantial variation in the δ 2 H fur values of bats within and among species at common locations [ 68 , 69 ]. Mean δ 2 H fur values may vary significantly among proximate roosts [ 55 , 69 ] and reproductive females may have fur that is depleted of 2 H compared to juveniles [ 66 , 69 ].…”
Section: Intrinsic Markers In Studies Of Bat Migrationmentioning
confidence: 99%
“…While there are strong transfer functions for many species, there is still substantial variation in the δ 2 H fur values of bats within and among species at common locations [ 68 , 69 ]. Mean δ 2 H fur values may vary significantly among proximate roosts [ 55 , 69 ] and reproductive females may have fur that is depleted of 2 H compared to juveniles [ 66 , 69 ]. Variation among species can be even more significant.…”
Section: Intrinsic Markers In Studies Of Bat Migrationmentioning
confidence: 99%